A model for business responses to global challenges and sustainable development. Issue 2 (9th January 2019) - Virakul, Busaya; Russ-Eft, Darlene F.
Abstract : Purpose: This study aims to validate a model of organizational performance embedding corporate social responsibility (CSR), corporate governance (CG) and sustainability concepts at a strategic level. The model has been created in response to two significant global influences: global challenges and sustainable development (SD). Design/methodology/approach: To validate the model created, executives from 10 of Thailand's leading companies that have received CSR, CG, or sustainability awards during 2010-2015 were asked to complete a questionnaire and were later interviewed. Findings: The findings indicate the appropriateness of the model in addressing the two significant global influences and highlight the critical issues in its implementation. Research limitations/implications: Types of interviewees who are information sources, organization's features such as size and industry and culture, appear to be critical factors in affecting the research findings and in limiting the interpretation and applications of the research model. All of those limitations have been explained in the research paper so that future research could be improved. Practical implications: The model presents additional knowledge in relation to SD, business strategy, organizational performance and organizational sustainability. It shows how businesses can participate and respond to SD by embedding CSR, CG and sustainability concepts at the strategic level. It also shows that the outcome of such an approach will help business organizations sustain their existence by balancing financial, social and environmental dimensions. Social implications: Business is one of the three key players (government, business and citizens) in managing global challenges and promoting SD. A business sector contains huge valuable resources (e.g. physical; financial; human; technology) for development capabilities. Therefore, this research shows a model which helps business organizations understand their significant role in SD. Originality/value: Due to increased human population, climate change and deterioration of natural resources, social thinkers all around the world have been warning the seriousness of global challenges and the importance of SD. However, not many studies combine and connect the key concepts of global challenges, SD, CSR, CG and sustainability, all together to address the important role of business organizations. This research answers/gives such overall picture through a field research work for validation.